Conceptual Framework for Designing an Expert Advisor System Based on Technical Indicators: Evidence from Malaysian Forex Traders - Zarith Sofia Zulkifli; Nurnadiah Zamri (PT. Delitekno Media Mandiri, 2026)
The evolution of algorithmic trading (AT) has dramatically transformed the Foreign Exchange (Forex) market by integrating computational intelligence into trading and decision-making processes. Despite these advancements, Malaysian traders remain challenged in adopting such systems, particularly due to limited technical expertise, inadequate adaptation to local trading practices, and a lack of customized automated tools. This concept paper proposes a framework for designing Expert Advisors (EAs) that incorporate technical indicators (TIs) aligned with Malaysian traders' preferences and prevailing market conditions. The framework integrates three core components: trader competency assessment, indicator-based strategy development, and EA system architecture design, aimed at improving trade accuracy, profitability, and risk management. A qualitative approach grounded in literature synthesis and contextual analysis is employed to construct the proposed framework. The resulting model offers a structured and context-sensitive approach that combines trader preferences, technological innovation, and ethical considerations, with practical implications for system developers, educators, and regulators. The originality of this study lies in its localization of EA design to Malaysian traders' needs, bridging the gap between advanced algorithmic tools and local market readiness, while providing a replicable model for other emerging markets adopting AT solutions.